2019
DOI: 10.1111/imb.12568
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide dissection of sex determination genes in the highly invasive whitefly species Bemisia tabaci Q/MED

Abstract: Sex determination genes are important regulators of reproduction as well as of the development of both behavioural and morphological sex characteristics. The sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), is an emerging insect pest worldwide. The recent release of the genome sequence of the highly invasive B. tabaciQ/MED allows us to investigate the mechanisms and genes involved in sex determination. The combined genome and transcriptome‐wide analyses identified 26 genes putatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Unmated females only give birth to haploid males, and mated females can give birth to both males and females [19]. Previously, we identified 26 sex-determining genes in B. tabaci and confirmed by RNAi the interaction between Btdsx and Bttra2 and their important role in male genital formation, as well as the relationship between Btix and female fertility [20][21][22][23]. In addition, we identified a number of candidate genes for female mating response by transcriptomic analysis [24].…”
Section: Introductionmentioning
confidence: 58%
“…Unmated females only give birth to haploid males, and mated females can give birth to both males and females [19]. Previously, we identified 26 sex-determining genes in B. tabaci and confirmed by RNAi the interaction between Btdsx and Bttra2 and their important role in male genital formation, as well as the relationship between Btix and female fertility [20][21][22][23]. In addition, we identified a number of candidate genes for female mating response by transcriptomic analysis [24].…”
Section: Introductionmentioning
confidence: 58%
“…The whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) is a worldwide agricultural pest with a haplodiploid reproductive system (Blackman and Cahill, 1998). Our laboratory previously identified 26 genes putatively associated with sex determination in B. tabaci and found that da, mle, and PSI undergo sexspecific splicing in B. tabaci, while Imp, dsx, and tra2 do not (Liu et al, 2016(Liu et al, , 2019Guo et al, 2018). Using RNAi experiments, we also found that Btdsx and Bttra2 affect each other and are important for male genitalia formation (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…The annotated sequences obtained from our previous study (Liu et al, 2019) were used to design full-length primers to amplify the Btix gene ( Table 1). The PCRs were performed using Es-Taq Master Mix (CWBIO, Beijing, China) under the following conditions: initial denaturation at 95 • C for 5 min, followed by 35 cycles of 95 • C for 30 s, 55 • C for 30 s, and 72 • C for 1 min, and a final extension at 72 • C for 10 min.…”
Section: Gene Cloning and Identification Of Alternative Splicing Varimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used for the screening of genes associated with various traits in sugarcane, such as sucrose accumulation [ 39 , 40 ], smut resistance [ 41 , 42 ] and the response to low nitrogen [ 43 ]. Transcriptome analysis was also used for the identification of sex-determining genes in many insects, such as Plutella xylostella [ 44 ], Phlebotominae sand flies [ 45 ], whitefly [ 46 ], Sogatella furcifera [ 47 ] and Zeugodacus tau (Walker) [ 48 ].…”
Section: Introductionmentioning
confidence: 99%